2012
DOI: 10.1016/j.vaccine.2012.08.056
|View full text |Cite
|
Sign up to set email alerts
|

Immune response to tetanus booster in infants aged 15 months born prematurely with very low birth weight

Abstract: Humoral and cellular response following a tetanus booster was similar in both groups. Premature infants exhibited lower levels of anti-tetanus antibodies at 15 months of age, with the lowest levels in those born at a gestational age of less than 32 weeks. Breastfeeding was associated with greater levels of antibody against tetanus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
6
1
Order By: Relevance
“…Our group has previously shown that preterm children born with mean gestational age of 29.9 weeks and mean birth weight of 1185 g tend to have a high rate of hospitalization during the first year of life for different causes (37.5%) (33). However, in the present study, only 4/28 (14.3%) children were born with gestational age below 34 weeks.…”
Section: Discussioncontrasting
confidence: 74%
“…Our group has previously shown that preterm children born with mean gestational age of 29.9 weeks and mean birth weight of 1185 g tend to have a high rate of hospitalization during the first year of life for different causes (37.5%) (33). However, in the present study, only 4/28 (14.3%) children were born with gestational age below 34 weeks.…”
Section: Discussioncontrasting
confidence: 74%
“…However, in other studies [ 27 29 ], 7-year-old children who were born at <29 weeks of gestational age, with birthweight <1000 g, and vaccinated in the first few weeks of life, presented with significantly lower concentrations of antibodies against diphtheria, tetanus, poliomyelitis, and HBV than their peers delivered at term. These findings suggest that gestational age and/or body weight at birth are determinants of post-vaccination immune response and IgG elimination rates.…”
Section: Discussionmentioning
confidence: 89%
“…The type of vaccine used for primary immunization against pertussis (acellular or whole-cell) seems to be a key determinant of long-term immunity; according to the literature, acellular vaccines provide shorter seroprotection later in life [ 27 , 28 ]. It is estimated that only 10% of children born at term and vaccinated with the acellular vaccine present with seroprotective levels of anti-pertussis IgG at 8.5 years after the last immunization; this justifies implementation of earlier booster strategies to control spread of this infectious disease [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study (scheme -2-4-6 months) obtained the same results: lower pertussis toxin antibody titers after 3 doses and their rise to the post-booster titer level in term infants at 1 year of age [15]. The work of S. Esposito et al, who revealed sufficient levels of specific immune globulins at the age of 5 years in most premature infants who undergone a three-stage vaccination (scheme -3-5-12 months), indicates the long-term preservation of protective levels [29]. A range of studies claim that premature infants with GA <31 weeks respond to the acellular vaccine administration not only humorally, but also cellularly -with the IFN γ production by peripheral mononuclear leukocytes and the interleukin (IL) 5 and IL 13 secretion in case of exposure to vaccinal antigens [30].…”
Section: Immunogenicity and Reactogenicity In Premature Infantsmentioning
confidence: 80%